Transplanted fibroblast cell sheets promote migration of hepatic progenitor cells in the incised host liver in allogeneic rat model. (12th March 2013) - Muraoka, Izumi; Takatsuki, Mitsuhisa; Sakai, Yusuke; Tomonaga, Tetsuo; Soyama, Akihiko; Hidaka, Masaaki; Hishikawa, Yoshitaka; Koji, Takehiko; Utoh, Rie; Ohashi, Kazuo; Okano, Teruo; Kanematsu, Takashi; et al.
Abstract: Cell sheet engineering has been noted as a new and valuable approach in the tissue‐engineering field. The objective of this study was to explore a procedure to induce hepatic progenitor cells and biliary duct structures in the liver. Sprague–Dawley rat dermal fibroblast (DF) sheets were transplanted into the incised surface of the liver of F344 nude rats. In the control group, an incision was made without transplantation of the DF sheets. Bile duct (BD)‐like structures and immature hepatocyte‐like cells were observed in the DF sheet transplant sites. These BD‐like structures were cytokeratin‐8‐positive, while the hepatocyte‐like cells were both OV‐6‐positive and α ‐fetoprotein‐positive as well. The proliferation and differentiation of liver progenitor cells were not influenced by hepatectomy. We also transplanted DF sheets transfected with a plasmid encoding the enhanced yellow fluorescent protein target to mitochondria (pEYFP–Mito) by electroporation, and found that the new structures were pEYFP–Mito‐negative. We observed new BD‐like structures and immature hepatocytes after transplantation of DF sheets onto incised liver surfaces, and clarified that the origin of these BD‐like structures and hepatocyte‐like cells was the recipient liver. The present study described an aspect of the hepatic differentiation process induced at the site of liver injury. Copyright © 2013 John Wiley & Sons, Ltd.